Unveiling the mechanism of calcitriol in treating type 2 diabetes mellitus: A combined network pharmacology and in vitro approach targeting ERS-related pathways - Fanqiang Zeng; Yimei Liao; Jianping Jiang; Chengjian Zhao; Shuihua Peng; Huijie Zhang; Hui Zou; Shudan Tan; Liya Qiao; Fan Liu; Juan Huo; Zhigang Yan; et al. (PLoS ONE, 2026)
Type 2 diabetes mellitus (T2DM) has emerged as a major global public health concern, characterized by increasing prevalence and serious complications that contribute substantially to societal healthcare costs. Concurrently, endoplasmic reticulum stress (ERS) has been increasingly appreciated as a central pathogenic mechanism underpinning the development and progression of T2DM. Calcitriol has been shown to have a beneficial effect in the treatment of T2DM. However, the therapeutic targets and potential mechanisms of calcitriol against T2DM through modulated ERS-related pathways remain poorly understood. To systematically investigate these mechanisms, we adopted an integrated approach combining network pharmacology, molecular docking and experimental validation. Initial network pharmacology analysis identified STAT3, HSP90AA1, MAPK1, and PIK3R1 as potential key targets mediating calcitriol’s anti-T2DM effects. These computational predictions were then experimentally validated using a high glucose (HG)-induced MIN6 cell model. Functional assessments using CCK-8 assays and flow cytometry demonstrated that calcitriol improved the survival of pancreatic β-cells and reduced glucose-induced cell death. Moreover, the results from real-time fluorescent quantitative PCR and western blot analysis revealed that calcitriol reversed the HG induced upregulation of STAT3, HSP90AA1, MAPK1 and PIK3R1 mRNA and protein levels in MIN6 cells. The findings from our study may offer insights into the underlying mechanisms through which calcitriol exerts its therapeutic effects on T2DM by targeting potential ERS-related pathways.